Repair of post polypectomy colonic perforation by Endoclip: a case report - Hormati,Ahmad (2015)
A 73-year-old woman was admitted to evaluate for iron deﬁciency anemia, increased serum creatinine, and ascites. Her colonoscopy revealed a polyp at the junction of sigmoid and descending colon, and after polypectomy, a 6 mm colonic perforation was seen. The perforation was detected by radiography and CT scan; and beside conservative management and antibiotics, her perforation was closed by using Endoclip. The patient was observed and discharged from hospital without any surgery 5 days later, and in follow-up there was no problem regarding perforation.